Time to Complete Retinal Vascularization After Anti-VEGF Among Preterm Neonates in Pakistan: Complete Retinal Vascularization After Anti-VEGF Among Preterm Neonates - Memon, Mariya Nazish; Jatoi, Asadullah; Mahesar, Mona Liza; Gilal, Imtiaz; Chand, Saroop; Kumar Narsani, Ashok; Maisam, Muhammad (Pakistan Journal of Health Sciences, 2025)
Retinopathy of prematurity (ROP) is a leading cause of preventable blindness in children. Anti-VEGF agents are widely used for treatment, but they pose concerns regarding delayed or incomplete retinal vascularization. There is limited local data on the vascularization timeline in Pakistani preterm neonates following anti-VEGF therapy. Objectives: To determine the time required to achieve complete retinal vascularization after intravitreal anti-VEGF injection in preterm neonates with ROP and to identify clinical predictors influencing this timeline. Methods: This prospective cohort study was conducted over 1.5 years from December 2023 to May 2025 at the neonatal nursery of the Pediatric Ward, Liaquat University of Medical and Health Sciences, Jamshoro. A total of 63 preterm neonates with treatment-requiring ROP received either Bevacizumab or Ranibizumab. Demographic, clinical, and treatment-related data were collected. Time to complete vascularization and postmenstrual age (PMA) at vascularization were recorded. ANOVA was used to assess statistical differences between subgroups. Results: The mean time to complete vascularization was 10.5 ± 2.0 weeks’ post-treatment, with a PMA of 44.5 ± 2.1 weeks. Delayed vascularization (>50 weeks) occurred in 8.5% and reactivation in 6.4% of neonates. Stage 3 ROP, Zone I disease, and Bevacizumab were associated with slightly longer vascularization times, but none of these comparisons were statistically significant (p>0.05). Conclusions: Retinal vascularization typically completes within 10–12 weeks after anti-VEGF therapy. Although not statistically significant, trends suggest extended follow-up is advisable in neonates with more severe disease or ZONE I ROP.